Eating disorders and disordered eating behaviors in female track and field athletes - Gabarajeva, N.; Vazne, Z. (LASE Journal of Sport Science, 2017)
Eating disorders (ED) and disordered eating behaviors (DEB) are more prevalent among athletes than in the general population. Female elite athletes participating in sports in which leanness is important are at yet higher risk for developing DEB and ED. The aim of this study is to determine the prevalence and the reasons of ED and DEB in female track and field athletes in Latvia. The participants are 18 - 41 year old female track and field athletes in Latvia having been the candidates of the Latvian National team in track and field at least for one season during the years 2015 - 2017. The methods used in this study are the scientific literature analysis, a survey: the EDE-Q 6.0, a case study: semi-structured interview and mathematical statistics. Is has been found that some of the participants of this study do present possible DEB. The development of DEB in female track and field athletes in Latvia has been aided by coach related pressure and critical comments regarding athlete`s weight, a strict reduction of food intake and athlete`s personality traits - perfectionism, overcoming oneself and striving towards an ideal. The results of this study suggest that it is necessary for track and field coaches and athletes to be educated about ED and DEB.